Genotyping and Phylogenetic Analysis of Fasciola Spp. Isolated from Sheep and Cattle Using PCR-RFLP in Ardabil Province, Northwestern Iran. - Mojgan Aryaeipour; Soheila Rouhani; Mojgan Bandehpour; Hadi Mirahmadi; Bahram Kazemi; Mohammad Bagher Rokni (Tehran University of Medical Sciences, 2014)
The aim of this study was to detect the genotype of Fasciola spp. in Meshkin-Shahr, Ardabil Province, northwestern Iran in different hosts using PCR-RFLP.The parasite hosts included cattle, and sheep. Overall, 70 adult flukes from livers of slaughtered animals were collected from the abattoirs of aforementioned area. The included 35 samples from infected sheep and 35 samples from 35 infected cattle. PCR-RFLP and sequence analysis of the first nuclear ribosomal internal transcribed spacer (ITS 1) region from Fasciola species were used to conduct the study.The fragment of approximately 700bp in all of the Fasciola samples was amplified. PCR products of ITS 1 were subjected for digestion by restriction enzyme. RsaI restriction enzyme was selected for RFLP method that caused the separation specifically of Fasciola species. Amplicons with the sequences of F. hepatica had a pattern of about 360, 100, and 60 bp band size, whereas F. gigantica worms had a profile of 360, 170, and 60 bp in size, respectively. Results based on PCR-RFLP analysis were confirmed by sequence analysis of representative ITS 1 amplicons. No hybrid forms were detected in the present study. All sheep were infected with F. hepatica but cattle were infected with both species.Both species of Fasciola are present in Ardabil. The method described here can be valuable for identification of Fasciola species in endemic parts for fasciolosis, regions with intermediate species and in that overlapping distribution area.